Pembelajaran Augmentasi Reality untuk Meningkatkan Pemahaman Hakikat Sains Sistematis Literatur Review - Elza Ardea Nadela; Niki Dian Permana; Mery Berlian; Rian Vebrianto (Natural Science, 2022)
Students' ignorance of science makes it difficult for educators to teach. Augmented Reality can help students and instructors complete the learning system. Truth enhancement is an innovation that incorporates 3D (3D) virtual items in a real 3D climate. The survey results show that in the learning process the students' lack of interest in learning. The lack of student interest in carrying out the learning process is caused by learning activities carried out only by the lecture method and giving questions on a regular basis. This research is intended as a training aid to help students attract more attention and interest in the learning process. AR innovations have been applied in various fields and in various areas of training. In the field of training, the extension of truth is used as a learning climate. The innovation of increased reality can also be utilized to understand scientific ideas by describing the construction of model items and theoretical ideas. The method used is a systematic literature review using PRISMA diagrams and using two digital libraries, namely Google Scholar and Google Scholar. So that the selected literature is relevant, the search uses the keywords "Agmented Reality Learning, Use of Augmented Reality Media in Understanding the Nature of Science". Furthermore, screening to get scientific article publications from 2016-2021 which discusses the development of augmented reality media in understanding the nature of science so that there are 8 articles that are appropriate. From this study, it was found that there is an inquiry learning model, the effectiveness of learning media and applications that use AR technology. From the research, it is hoped that students will experience increased learning from all aspects and all points of view. It can be concluded that the use of expanded reality media can build the advantages of students' interest and understanding in learning. In future research, it is expected to use more journal sources so that they can deepen the research results.